Peningkatan Kesadaran Pancasila Sebagai Dasar Negara Melalui Sosialisasi Anti Tawuran Antar Pelajar Di Sekolah Menengah Pertama Negeri 30 Kota Padang - Diva Zahara; Dion Agung Pratama Reja Antarmefia; Zahra Karmila; Deniza Karmila; Muhammad Feblianzeo; Azmi Fadhilah; Eka Suci Rahmadini; Ilham Ridhollah; Rafa Alnanda Jodi; Elwidarifa Marwenny (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Increasing Pancasila as the basis of the state can be achieved through socialization that emphasizes the values ​​of tolerance and unity among students. This effort aims to prevent brawls between students and build awareness of the importance of maintaining harmony in society. This socialization is focused on increasing students' understanding of Pancasila as the state ideology, as well as instilling the values ​​of mutual respect and cooperation. Implementation methods include seminars, discussions, and involvement of community leaders and educators, as well as the use of social media to reach more students. The expected results of this program are increased student awareness of the importance of Pancasila, a reduction in the number of brawls between students, and the formation of a student community that supports each other and respects differences. With these steps, it is hoped that Pancasila can become stronger as the basis of the state and become a guideline in students' daily lives.